Solving Unequal-Area Dynamic Facility Layout Problems Based On Slicing Tree Representation and Simulated Annealing - Asl, Ali Derakhshan (2015)
Facility design problems relate to the location or design of facilities or departments in a given area. This study deal with unequal-area dynamic facility layout problems in order to minimize the sum of the shifting costs and the sum of the material handling costs. The slicing tree structure has not been applied to these problems so far. In this paper, unequal-area dynamic facility layout problems based on the slicing tree representation are investigated. Due to their complexity, they could not be solved within a reasonable computational time by exact methods when the number of departments increases. Hence, a simulated annealing approach is suggested for solving them. The simulated annealing approach is tested with some problem instances taken from the literature. According to the results, this algorithm generates better solutions in comparison with other methods.